Caracterización y clasificación de la red hidrográfica de la cuenca del río Bobo, departamento de Nariño - Colombia - Mora, Victoria Benavides [UNESP]; Pissarra, Teresa Cristina Tarlé [UNESP]; Galbiatti, João Antonio [UNESP] (My University, 2009)
The object of this work was to make a morphometric characterization of the Bobo river watershed in the Nariño department in Colombia. A map was created from topographical maps (1:25.000 scale) using the drainage network and the limit of each 2nd order microbasin as database. Dimensional, drainage network and relief morphometric parameters were evaluated for a later hy-drological study. The drainage area was 224.97 km2, having a 71.31 km perimeter. The Bobo river watershed is considered to be 6th order and has 176 2nd order drainage channels, 34 3rd order drainage channels, 9 4th order drainage channels and 3 5th order drainage channels. Average drainage density is 3.71km/km2, reflecting its high density, having strong, dissected geological formation. The area has a typical Andean land-use pattern, having native wooded vegetation, traditional transitory potato and vegetable growing predominating.
Morphometric characterisation and classification of the Bobo river watershed in the Nariño department, Colombia
Keywords: Morphometry; Physical parameter; Watershed